Soldiers initiate foraging activities in the subterranean termite, Heterotermes tenuis - Casarin, Fabiana Elaine [UNESP]; Costa-Leonardo, Ana Maria [UNESP]; Arab, Alberto [UNESP] (Oxford University Press (OUP), 2008)
Caste polyethism has been recorded in some termite species, however the foraging behavior of subterranean termites remains poorly known. Heterotermes tenuis Hagen (Isoptera: Rhinotermitidae) is a subterranean termite that is native to Brazil and is an agricultural and urban pest. The aim of this study was to investigate which caste acts as scouts when searching for food sources and determinate the percentages of each caste present in the foraging territories of field colonies of H. tenuis. Our results showed no significant differences among the caste proportions present in the foraging territories of the three colonies studied in the field. Laboratory experiments showed that minor soldiers were the most frequent initiators of foraging activities. This result suggests that the exploratory phase of the foraging behavior may be regulated by the number of soldiers present in the foraging territories of each colony.
Keywords: Foraging behavior; Heterotermes tenuis; Polyethism; Soldier; Termites